The Cross‐Section of Credit Risk Premia and Equity Returns - FRIEWALD, NILS; WAGNER, CHRISTIAN; ZECHNER, JOSEF (Journal of Finance, 2014)
ABSTRACT We explore the link between a firm's stock returns and credit risk using a simple insight from structural models following Merton ( ): risk premia on equity and credit instruments are related because all claims on assets must earn the same compensation per unit of risk. Consistent with theory, we find that firms' stock returns increase with credit risk premia estimated from CDS spreads. Credit risk premia contain information not captured by physical or risk‐neutral default probabilities alone. This sheds new light on the “distress puzzle”—the lack of a positive relation between equity returns and default probabilities—reported in previous studies.